Peran Kendal sebagai kawasan ekonomi khusus dalam transformasi ekonomi: analisis strategis dan implementasi melalui matriks SWOT - Sarfiah, Sudati Nur; Septiani, Yustirania; Sugiharti, Rr. Retno (Nur Science Institute, 2023)
Since being designated as a Special Economic Zone (KEK), Kendal is expected to be able to become the axis of the economy on the island of Java. The establishment of KEK especially KEK Kendal is expected to stimulate investment and business growth which will have an impact on increasing employment and reducing poverty. Nationally, the purpose of creating KEK is economic equity, especially in terms of income and the competitiveness of national products. The establishment of a special economic zone requires careful preparation and commitment from all interested parties to support the implementation of the area's activities. The preparations include policies and institutions, incentives and financing, as well as infrastructure completeness according to the spatial plan. While special economic zones can offer many benefits, on the other hand many special economic zones have been criticized for their high social and economic costs. The purpose of this research is to formulate an appropriate strategy for the development of the Kendal area as a special economic zone. The SWOT matrix that has been formed has described how the strategy can be carried out in the future.